Menyebarkan Nilai Islam Di Kalangan Gen-Z: (Studi Kasus Strategi Komunikasi Dakwah Digital Pada Akun Tiktok Kadam Sidik) - Ika; Az-Zahra, Jenny; Razzaq, Abdur; Nugraha, Muhamad Yudistira (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
Generation Z is a group that grew up in the digital era, where social media has become an integral part of their lives. This has driven changes in da'wah strategies to be more relevant and effective in spreading Islamic values. This study aims to analyze the digital da'wah communication strategy in spreading Islamic values ​​to Gen Z through a case study of the TikTok account Kadam Sidik. Using a descriptive qualitative method, this study examines the types of content, message delivery techniques, and the impact of interactions between da'wah and audiences. The results of the study show that Kadam Sidik applies a communication strategy based on storytelling, humor, and the use of social media trends to attract attention and increase understanding of Islam among Gen Z. In addition, active interaction with the audience through comments and live streaming is an important factor in building closeness and strengthening da'wah messages. This study confirms that a creative, communicative da'wah approach that is in accordance with the characteristics of digital media can increase the effectiveness of spreading Islamic values ​​to the younger generation.